Impact assessment report at the meso-level: Experiences from Ghana - Manoti, Dismas; Kikulwe, Enoch; Carbonell Barlis, Angelica; Dalaa, Mustapha Alasan; Obeng, Faustina; Mahama, Obed Kwaku (2025)
This report presents a qualitative impact assessment of the Accelerating Impacts of CGIAR Climate Research for Africa (AICCRA) project in Ghana, focusing on how the program strengthened meso-level institutions (“next users”) and expanded the delivery and uptake of Climate Information Services (CIS) and Climate-Smart Agriculture (CSA) innovations. Ghana’s agriculture sector, dominated by rainfed smallholder systems faces deep vulnerabilities arising from erratic rainfall, prolonged dry spells, rising temperatures, and systemic barriers such as weak extension systems, fragmented climate governance, inadequate data-sharing mechanisms, and socio-economic constraints that disproportionately affect women and low-literacy farmers. AICCRA Ghana was designed to address these structural bottlenecks by enhancing institutional capacity, establishing coordinated pathways for scaling CIS/CSA, and aligning interventions with national climate policy frameworks.